Implementation of Gamification Technology to Improve Motivation and Understanding of IPAS Subject Material - Ayunina Valentina Zulfa; Ratnasari Diah Utami (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to evaluate the impact of gamification on increasing learning motivation and understanding of science subject material among fourth-grade elementary school students. Specifically, this study emphasizes the mechanisms by which gamification components can produce a more engaging, interactive, and efficient learning experience to increase student participation and conceptual comprehension.Methodology: This study used a one-group pretest-posttest design and quantitative methodology. A total of 21 fourth-grade students participated in this study. A learning motivation questionnaire and material comprehension test with pre-tests and post-tests were used to collect data. In addition, student participation during the gamification-based learning process was observed. To assess the differences between the pretest and posttest, the data were analyzed using a paired sample t-test, validity and reliability tests, and normality tests.Results: The results of the t-test for paired samples show a significant increase in students' understanding of IPAS material, as seen from the significance value (2-tailed) of 0.000, which is less than 0.05. The effectiveness of gamification in improving learning outcomes is proven by the higher average posttest scores compared to the pretest scores. In addition, students' motivation to learn increased from moderate to high, in line with existing motivational concepts. Furthermore, observations show that this approach creates a more competitive, energetic, and enthusiastic learning atmosphere in a constructive context.Applications/Originality/Value: This research contributes significantly to the implementation of learning at the elementary school level by demonstrating the effectiveness of gamification in increasing intrinsic motivation and IPAS comprehension competencies. The novelty aspect of this research is evident in the adaptation of game components that are aligned with the developmental characteristics of fourth-grade students, which results in a more meaningful and engaging learning experience. The implications of this research can be used as a scientific reference for education practitioners, schools, and academics in designing learning innovations that are integrated with learning technology.